Kualitas kerupuk susuyang dibuat dengan perbedaan jenis tepung - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
Five kinds of flour were used to make five different milk chips, i. e.: 1) rice flour, 2) wheat flour, 3) cassava flour, 4) sago flour and 5) all of the four mixed in equal parts. Ten liters of milk were divided into five parts subjected to mixing with the above kinds of flour, each was then divided into two equally treated a) without and b) with sodium bicarbonate. Quality parameters analyzed were enlargement test and chemical tests of protein, fat, moisture and ash for both the doughs and chips. Analysis of variance was done using factorial design of 2x2x5. The quality of sun-dried milk chip was good enough as moisture contents were ranging from 10.93 to 14.99%. The use of sodium bicarbonate was effective for making better milk chips. However, it depends on the kind of flour used. The best enlargement was achieved by the use of mixed flour (316.67%) while the uses of cassava and sago flours produced 309.22 and 181.29% enlargements, respectively. The uses of rice and wheat flours did not produce good milk chips, since the enlargements were only 19.48 and 77.94%, respectively. The protein contents varied depending on the kind of flour's protein content. The highest protein content (11.75%) was produced from the use of wheat flour, while the others were 8.81% (rice flour), 6.88% (mixed flour), 2.65% (cassava flour) and 2.56% (sago flour).